2017
DOI: 10.1007/s11071-017-3504-3
|View full text |Cite
|
Sign up to set email alerts
|

Stability investigation of velocity-modulated gear system using a new computational algorithm

Abstract: By considering the lubricant in gear system, one degree-of-freedom model is set up which incorporates the pinion's speed and the drag torque as the excitation sources. By introducing a permissible error (ε), a new computational algorithm using double-changed time steps is proposed in order to reduce the ill-conditioning arising from the numerical stiffness of the gear system and validated by comparison with Runge-Kutta-Fehlberg integration scheme. Then, the influences of the lubricant on the vibration of the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 58 publications
(77 reference statements)
0
3
0
Order By: Relevance
“…But this phenomenon is not obvious when the double pairs of teeth transits to the single tooth pair. Therefore, the stronger vibration and noise of the gear system generally occurs on the driving side [40]. Bifurcation diagram is an effective means to observe the nonlinear dynamic response of gear system dynamics.…”
Section: Resultsmentioning
confidence: 99%
“…But this phenomenon is not obvious when the double pairs of teeth transits to the single tooth pair. Therefore, the stronger vibration and noise of the gear system generally occurs on the driving side [40]. Bifurcation diagram is an effective means to observe the nonlinear dynamic response of gear system dynamics.…”
Section: Resultsmentioning
confidence: 99%
“…From the perspective of electromechanical coupling, Jiang et al 9,10 revealed the influence of electromagnetic effects on the natural frequency of the gear system. Considering the role of lubrication, Liu et al 11 established a model of the gear system, and proposed a new calculation method to study the dynamic characteristics. Based on the finite element method theory, Ouyang et al 12 proposed a new gear-roller-bearing system dynamic model with time-varying characteristics and contact nonlinearity.…”
Section: Introductionmentioning
confidence: 99%
“…Actually, most of the solution algorithms available in the literature can not be immediately applied to examine this problem even used the ''stiff'' solvers, because the Jacobian matrix of the linearizing gear system is discontinuities and varying around different operation point [41]. Hence, it is vital important to develop a NCA which does not use the Jacobian matrix to avoid this ''stubborn'' as suggested in the paper [7,42].…”
Section: Introductionmentioning
confidence: 99%